Efektifitas Komunikasi Antarpribadi Pustakawan pada Pelayanan Sirkulasi Perpustakaan Politeknik Negeri Lampung - Brama Sari; Purwanto Putra (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Interpersonal communication plays a crucial role in enhancing library service quality, particularly in the circulation section, which serves as the primary point of interaction between librarians and users. This study aims to analyze the effectiveness of librarians’ interpersonal communication at the Politeknik Negeri Lampung Library based on Joseph A. DeVito’s five principles: openness, empathy, supportiveness, positiveness, and equality. The research employs a descriptive qualitative method through observation, interviews, and literature review. The findings reveal that interpersonal communication among librarians is effective. Openness is reflected in friendly responses to user inquiries; empathy is shown through understanding users’ needs; supportiveness appears in providing alternative solutions; positiveness is demonstrated through politeness and hospitality; and equality is maintained through fair treatment without discrimination. Effective communication contributes significantly to users’ satisfaction, comfort, and loyalty, while strengthening the library’s image as a friendly, inclusive, and professional information center. The study suggests: (1) conducting regular training to improve librarians’ communication competence, (2) utilizing digital communication technologies, (3) implementing periodic service quality evaluations, and (4) developing interactive information literacy programs to foster active engagement between librarians and users.